NEW CHALLENGES IN ASEAN REGIONAL MARKET: INTERNATIONAL TRADE FRAMEWORK ON HALAL STANDARD - Eva Johan (Faculty of Law, Universitas Jenderal Soedirman, 2018)
The use of non-tariff protection increased during 1980s. One of Non-tariff measures which have been deployed by countries is safety and health standards/technical specifications. In many Muslim countries, Halal standard has essential part in protecting consumer rights. National labeling laws must seek a balance between labeling requirements and certification to minimize barriers to the free trade. The problem is every nation has own Halal Standard. This could result trade dispute among parties since import product cannot enter local market based on different Halal Standard. This situation remains as non-tariff barriers to free trade. By capturing the differences of Halal Standard in some ASEAN countries, the result shows some challenges rise for ASEAN to create one unified Halal Standard framework in order to gain strong ASEAN single market in the future. Keywords: non-tariff barriers, halal, standard, international trade.